Perlindungan Hukum Terhadap Kesejahteraan Anak Dalam Kasus Perceraian Menurut Kitab Fathul Qarib - Ahmad Misbakh Zainul Musthofa (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
Child custody (hadhanah) is a crucial legal issue following divorce, directly impacting children's emotional stability and overall well-being. Islamic law affirms that parental responsibilities continue even after divorce, with hadhanah serving as a central consideration. This study explores the concept of hadhanah in Fathul Qarib al-Mujib by Shaykh Muhammad bin Qasim al-Ghazi, a key reference in the Shafi’i school of jurisprudence, and assesses its relevance to Indonesia’s legal system. Positioned within normative-juridical research, this study compares Islamic jurisprudence with Indonesia’s positive law, particularly the Compilation of Islamic Law (KHI) and Law No. 35 of 2014 on Child Protection. Utilizing qualitative methods through library research, the study finds that Fathul Qarib prioritizes the mother as the primary custodian of children below the age of discernment (mumayyiz), except where disqualifying factors are present. The findings reveal that while Indonesia’s legal framework is generally aligned with Islamic jurisprudence, implementation remains problematic—particularly in monitoring and enforcing custody arrangements post-divorce. This study contributes to the development of child protection policy in Indonesia’s religious courts by advocating for more structured legal mechanisms to safeguard children's rights after parental separation.